Praktik Media Interaktif Dalam Meningkatkan Kondisi Kelas Pada Pembelajaran Bahasa Indonesia Di Sekolah Dasar - Wa Ode Delsi Mecriyani; Muhammad Yusnan; Marsanda Marsanda; Sindi Cahyani; Melisa Melisa (Journal of Humanities, Social Sciences, and Education, 2025)
This research is a literature review aimed at examining the practice of using interactive media in Indonesian language learning in elementary schools and its impact on classroom conditions. Interactive media has become an important tool in transforming learning from a conventional approach to a more dynamic and participatory one. In the context of Indonesian language learning, interactive media can create a conducive classroom atmosphere, increase learning motivation, and strengthen students' understanding of the learning material. The literature search was conducted by reviewing various scientific sources, both from accredited national journals and elementary education seminar proceedings. The study results indicate that interactive media such as learning videos, digital educational games, interactive quizzes, and technology-based applications can increase student engagement, improve classroom management, and build students' emotional and cognitive engagement with Indonesian language materials. The five main aspects identified in this study include increased student engagement, more effective classroom management, improved understanding of the material, development of communication skills, and the creation of a pleasant learning atmosphere. Therefore, the integration of interactive media in Indonesian language learning in elementary schools needs to be continuously developed through teacher training, infrastructure provision, and collaboration among educational stakeholders.